Peran Logistic Performance Terhadap Customer Loyalty dengan Customer Satisfaction sebagai Variabel Intervening (Studi Kasus E-Commerce) - Narohito, Yosapat Parningotan; Rahardjo, Sri; Arubusman, Dian Artanti (Dinasti Research, 2025)
This study aims to analyze the effect of logistic performance on Customer Loyalty in the context of e-commerce, with Customer Satisfaction as a mediating variable. Three dimensions of logistic performance are examined: Logistic Service Quality, Cost Delivery, and Integration Process. A quantitative approach is used with descriptive and inferential analysis techniques. Data were collected through an online survey of logistics service users in e-commerce platforms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Logistic Service Quality has a significant negative direct effect on Customer Loyalty, suggesting an anomaly in customer expectations toward logistics services. Conversely, Cost Delivery and Integration Process show significant positive effects on Customer Loyalty. Regarding Customer Satisfaction, Logistic Service Quality and Cost Delivery have positive impacts, while Integration Process has a negative influence. Furthermore, Customer Satisfaction significantly increases Customer Loyalty, reinforcing its mediating role in the model. The mediation analysis reveals that Customer Satisfaction successfully mediates the relationship between Logistic Service Quality and Customer Loyalty, turning a negative direct effect into a positive indirect one. However, for the Integration Process, an indirect negative effect on Customer Loyalty through Customer Satisfaction is observed, indicating that complex or user-unfriendly systems may reduce Customer Satisfaction and loyalty. These findings imply that logistics companies should not only focus on cost efficiency and technological integration but also consider customer comfort and satisfaction to foster long-term loyalty in the e-commerce ecosystem.